Business analysis & valuation using financial statements - Palepu, Krishna G.; Healy, Paul M. (South-Western Cengage Learning, 2013)
Shows how business analysis and valuation framework can be applied to a variety of decision contexts: securities analysis, credit analysis, corporate financing policies analysis, mergers and acquisitions analysis, and governance and communication analysis.